(untitled) (Advancements in Homeopathic Research, 2022)
You turn many pages of our Homoeopathic Journals and you find cases where in many Authors have/had cured cases of chronic miasmatic nature e.g.; diabetics, rheumatic arthritis, asthma, gastric ulcer, renal failure, etc.; within 3 to 6 months. Some cases are reported that even they have cured cancer by single medicine with single dose of high potency, Breast tumour was cured with single dose of high potency of medicine. What for and whose for such reported cases? Have they achieved mastery of Homoeopathy and reported these cases? Do our Editors realise what harm were/ was done to Homoeopathy with such imaginary cases by publication? Are we not faithful and sincere to Homoeopathy? Homoeopathy has certain limitations that we have to realise. What are/were supporting evidences e.g.; X-Ray, CT, CT-PT, Tumour Markers and Blood reports, before and after for such cases etc? We have to be human in reporting cases for our science of Homoeopathy and for the humanity. Nobody is master of Homoeopathy or of any science.